The sociology of health, illness, and health care a critical approach - Weitz, Rose 1952- (Cengage Learning, 2020)
The sociology of health, illness, and health care : a critical approach, 8th edition covers both micro- and macro-level topics while exposing the sociological and ethical dilemmas of modern health care and asking students to question their previously held beliefs about health and illness. Thorough discussions of health and health care emphasize how social forces can prevent or foster illness, affect cultural ideas about illness and disability, structure health care institutions, and affect the lives of health care workers. Race, class, gender, and disability issues are highlighted throughout and the social causes of health and illness in less developed nations and the diverse ways that nations provide (or don't provide) health care are also explored -- Provided by publisher.